2012
DOI: 10.1007/s00467-011-2070-z
|View full text |Cite
|
Sign up to set email alerts
|

Henoch–Schönlein purpura with hypocomplementemia

Abstract: Hypocomplementemia associated with HSP is a transient phenomenon. The incidence of significant sequelae such as HSPN between patients with and without hypocomplementemia does not differ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 18 publications
(42 reference statements)
4
21
1
4
Order By: Relevance
“…HSP has also been regarded as an immune complex disease; however, hypocomplementemia with low serum or plasma C3 and/or C4 levels was not commonly shown and usually transient in patients with acute HSP [23,24]. In the present study, the results showed the serum levels of C3 and C4 in all 30 HSP children at both acute and convalescent stages were within normal ranges.…”
Section: Discussionsupporting
confidence: 42%
“…HSP has also been regarded as an immune complex disease; however, hypocomplementemia with low serum or plasma C3 and/or C4 levels was not commonly shown and usually transient in patients with acute HSP [23,24]. In the present study, the results showed the serum levels of C3 and C4 in all 30 HSP children at both acute and convalescent stages were within normal ranges.…”
Section: Discussionsupporting
confidence: 42%
“…17 13.9% (47/338) of HenochSchönlein purpura patients was reported to present with low C4 levels. 32 In the present study, a high prevalence (19.34%) of low C4 levels was also detected in the IgAN patients. C4-mediated lectin pathway is involved in IgAN providing evidences as follows: in IgAN, polymeric IgA could bind to the mannan-binding lectin domain to activate lectin pathway resulting in renal C4 deposition.…”
Section: Discussionmentioning
confidence: 56%
“…Some children with HSP present with accompanying hypocomplementaemia, although these children do not necessarily present with nephropathy; thus, serum complement level decrease has no relevance to HSP severity or the development of HSPN . However, the hypocomplementaemia seen in our patient improved with the amelioration of clinical symptoms, including proteinuria and general oedema.…”
Section: Discussionmentioning
confidence: 56%